The Influence of Firm Size on the Effects of Islamic Corporate Social Responsibility, Independent Commissioners, and Institutional Ownership on Corporate Performance - Azizah Arifiana; Taufikur Rahman (Center for Indonesian Accounting Studies, 2026)
Research Objective – This study aims to analyze and determine the effect of Islamic Corporate Social Responsibility (ICSR), independent commissioners, and institutional ownership on company performance with firm size as a variable moderation in manufacturing companies listed in the Jakarta Islamic Index (JII 70) during the 2020–2024 period. Furthermore, this study examines the moderating role of firm size in the relationship between ICSR, independent commissioners, institutional ownership, and company performance. Method: This study employed a quantitative approach using secondary data obtained from annual reports and sustainability reports of manufacturing companies listed in JII 70 during the 2020–2024 period. The sample was selected using a purposive sampling technique based on predetermined criteria. Data were analyzed using panel data regression with Eviews 13 software. Findings: The results indicate that Islamic Corporate Social Responsibility (ICSR) has a negative and insignificant effect on company performance. Independent commissioners have a negative and insignificant effect on company performance, while institutional ownership has a positive and significant effect on company performance. Firm size can not moderate the relationship between ICSR, independent commissioners, and company performance. However, firm size can moderate the relationship between institutional ownership and company performance. Theoretical and Policy Implications – The findings support stakeholder and agency theories, emphasizing the importance of social responsibility disclosure and corporate governance mechanisms in improving company performance. Companies are encouraged to enhance the quality of ICSR disclosure and strengthen governance practices to achieve sustainable performance improvement. Research Novelty - The novelty of this study ;ies in examining firm size as a moderating variable in the relationship between ICSR, independent commissioners, institusional ownership, and the performance of manufacturing companies listed in JII 70 during the 2020-2024 period.